2014
DOI: 10.15690/vramn.v69i11-12.1181
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Life Quality in Children with Phenylketonuria

Abstract: Background: Phenylketonuria (PKU)-the most common inherited disorder of amino acid metabolism, identified in Russia by neonatal screening. The results of dietary treatment demonstrate a positive effect. However, the quality of PKU patients life remains unknown. Objective: The aim of the study was to assess the quality of PKU children life in comparison with their healthy peers, also depending on the treatment onset and the patient's age. Methods: The study involved 64 pairs-PKU child and one of his parents. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Two studies showed results similar to ours. One study conducted in the Russian Federation, using the same questionnaire as in the present study, showed statistically significant lower scores for PKU children when compared to healthy peers in all PedsQL core scales ( 34 ). Lower HRQoL scores, assessed by the Child Health Questionnaire (CHQ), were also demonstrated in a group of children and adolescents in Italy ( 35 ).…”
Section: Discussionsupporting
confidence: 64%
“…Two studies showed results similar to ours. One study conducted in the Russian Federation, using the same questionnaire as in the present study, showed statistically significant lower scores for PKU children when compared to healthy peers in all PedsQL core scales ( 34 ). Lower HRQoL scores, assessed by the Child Health Questionnaire (CHQ), were also demonstrated in a group of children and adolescents in Italy ( 35 ).…”
Section: Discussionsupporting
confidence: 64%
“…So, the host dietary pattern will have a profound effect on the microbiota, favoring the growth of species that uses these fuel sources, and this diet-induced microbial structure will have a crucial impact on host physiology and disease process (Figure 4) [205]. There are some studies evaluating overweight and/or obesity prevalence in patients with PKU; this is mainly in pediatric patients [127,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230], but also in mixed pediatric and adult populations [182,191,[231][232][233][234] or only adults [181,[235][236][237][238] reporting different Nutrients can directly interact with microorganisms to promote or inhibit their growth, shaping the gut microbial community. Also, diet-derived antigens and compounds can shape the gut microbiota in an indirect fashion by affecting host metabolism and its immune system.…”
Section: Nutrition Therapy: How It Modulates Microbiota and Microbiom...mentioning
confidence: 99%
“…There are some studies evaluating overweight and/or obesity prevalence in patients with PKU; this is mainly in pediatric patients [127,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230], but also in mixed pediatric and adult populations [182,191,[231][232][233][234] or only adults [181,[235][236][237][238] reporting different results. This has been recently reviewed [1,239], and cardiovascular risk through MetS concerns not only increased body weight but also increased body fat and, more precisely, increased visceral and other ectopic fat deposition [59].…”
Section: Cardiometabolic Risk Factors In Patients With Pkumentioning
confidence: 99%